Unusual Nucleic acid nanostructures based on G-quadruplex DNA - Miguel Angel Méndez (ACI Avances en Ciencias e Ingenierías, 2015)
A nano-assembly based on non-canonical DNA structures is reported. For the nanofabrication of a DNA-based structure the self-assembly of guanine quadruplex (Hoogsteen base pairing) and double-stranded DNA (Watson-Crick base pairing) was exploited. In general, an important number of nanostructures have being build exploiting the base pairing capability of canonical double stranded DNA. There are alternative approaches for construction using other DNA elements such as G-quadruplex, I-motifs, or triplexes. As a proof of principle, we have previously reported the use of duplex DNA (short synthetic DNA oligonucleotides) with sections of miss paired sites able to mediate formation of tetramolecular sections (G-quadruplex DNA prove) in order to ensemble the components into high molecular weight structures. Gel electrophoresis as well as atomic force microscopy show the formation of nanofibers. Gel electrophoresis as well as circular dichroism gave evidence of the presence of G-quadruplex sections. From AFM we estimated that the structures lengths expand from 250 to 2,000 nm with heights from 0.45 to 4.0 nm. Here we present another example of such nanofibers. We suggest that similar methodologies can be used to build more complex nano-structures that will exploit the properties of different DNA nano-oddities into functional applications.